Apple Inc Advertising Strategy - Rd Rafaida Putri Rahmania W (DINASTI RESEARCH, 2022)
This study aims to find out the results of an analysis of Apple Inc. in developing its marketing advertising strategy, especially related to the increase in advertising that is Apple's trademark. The method used in this study uses qualitative research methods and literature review. The results of this study indicate that Apple adapts User Generated Content (UGJ) to promote its products on social media, namely product placement on influencers/public figures, which are commonly called endorsements and